Pervasive computing and the networked world : Joint International Conference, ICPCA/SWS 2013, Vina del Mar, Chile, December 5-7, 2013. Revised Selected Papers - Vargas-Vera, Maria; Hu, Bo; Zu, Qiaohong (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the Joint International Conference on Pervasive Computing and Web Society, ICPCA/SWS 2013, held in Vina de Mar, Chile, in December 2013. The 56 revised full papers presented together with 29 poster papers were carefully reviewed and selected from 156 submissions. The papers are organized in topical sections on infrastructure and devices; service and solution; data and knowledge; as well as community.